2019
DOI: 10.1002/jcp.29233
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the prognosis and biological significance of HMGB1, HMGB2, and HMGB3 in gastric cancer

Abstract: High mobility group box (HMGB) consists primarily of HMGB1, HMGB2, and HMGB3 proteins. Although abnormal HMGB expression is associated with various tumors, the relationship with gastric cancer (GC) remains unclear. In this study, HMGB1, HMGB2, and HMGB3 expression was analyzed using the Oncomine and TCGA databases. Correlations between HMGB1, HMGB2, and HMGB3 and clinicopathological factors were analyzed. cBioPortal was used to analyze HMGB1, HMGB2, and HMGB3 genetic alterations and its gene regulation network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…It can bind to the chromatin in an atypical DNA structure (e.g., single-stranded DNA) and bend the DNA to increase its flexibility 23 25 . Unlike HMGB1 and HMGB2, HMGB3 is expressed at low levels in normal cells but often overexpressed (up to 20-fold) in cancer cells 26 . Moreover, HMGB3 is a marker of haematopoietic stem cells, and hence, HMGB3-deficient cells cannot regenerate bone marrow for a long time 27 .…”
Section: Introductionmentioning
confidence: 99%
“…It can bind to the chromatin in an atypical DNA structure (e.g., single-stranded DNA) and bend the DNA to increase its flexibility 23 25 . Unlike HMGB1 and HMGB2, HMGB3 is expressed at low levels in normal cells but often overexpressed (up to 20-fold) in cancer cells 26 . Moreover, HMGB3 is a marker of haematopoietic stem cells, and hence, HMGB3-deficient cells cannot regenerate bone marrow for a long time 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Six articles including 846 patients were therefore finally included for data extraction. [12][13][14][15][16][17] All the included studies analyzed the clinicopathological value of HMGB1 in GC. The detailed search strategy is shown in Figure 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…24 Many studies have confirmed that HMGB1 is highly expressed in various cancers and promotes the development of cancers. 25,26 Di et al reported that HMGB1 is upregulated in ESCC and modulates the proliferation and radioresistance of ESCC. 27 In our study, we observed that circLPAR3 silencing could hinder HMEB1 expression, whereas this repression could be reversed by inhibition of miR-375 or miR-433.…”
Section: Discussionmentioning
confidence: 99%